Storying domestic violence: constructions and stereotypes of abuse in the discourse of general practitioners - Mildorf, Jarmila (Frontiers of narrative, 2007)
Narrative : theoretical background -- Domestic violence and the role of general practice : a narrative-analytic approach -- Signs of abuse : "classic" disclosures and narrative trajectories -- Setting the scene of abuse : metaphors and spatiotemporal mapping -- Mythologizing time, mythologizing violence : backgrounds and explanations of domestic abuse -- Agents of their own victimization : the women's role in the GPs' narratives -- Evaluating abuse : storied knowledge and salient facts